Client Decision-Making Criteria on the Property Insurance Market - Lubaś, Magdalena (Journal of Finance and Financial Law, 2021)
Consumers wanting to guard against losses resulting from unforeseen random events, decide to buy insurance. It is recognized that their decisions are often irrational. The aim of the study was to determine the importance attributed by consumers to the most important criteria when choosing insurance. The study was conducted by means of a diagnostic survey using the CAWI technique in January 2020 on a group of 150 people. The results showed that the most important factors which consumers are guided by when choosing their insurance are: price, attractiveness of the offer and terms of the contract.